Transfers of Aurodan Oral Traditions of Yahadian Congregation of the Asy-Syahadatain Cirebon Congregation to Form the Short Film of the "Lentera" Theater MTs and SMK Nurul Huda Losari - S., Ahmad Maskur; Sumiyadi,; Iskandarwassid, (International Journal of Psychosocial Rehabilitation, 2020)
A As an ancestral inheritance, oral traditions in the archipelago continue to show their existence even though some have begun to be no longer visible in society due to the influence of cultural change due to the effects of globalization. Through oral media oral traditions become the inheritance of values from generation to generation. But in reality, this oral tradition in the middle of the current generation of society is being forgotten because the process of inheritance is less effective. This is the background of this research. The purpose of this study is to describe the preservation model of Nadoman poetry texts in the aurodan oral tradition by transferring a "short film" vehicle at the MTs and SMK Nurul Huda Losari lantern theater. Qualitative research with an ethnographic approach. This research was designed with the aim of creating a vehicle transfer model in the form of a short film from Nadoman Aurodan Asy-Syahadatain's poetry tradition of Cirebon as a "Short Film" made by the school theater group "Lentera". This study uses basic data, namely phenomena and social interactions on the project of nadoman poetry text vehicle in the aurodan tradition. General data collection is done by observation and interviews. The result of this study is to find a model for nadoman poetry vehicle in the aurodan yahadian tradition which is very important as a preservation model for the aurodan tradition by raising it as one of the young generation's creativity products in the form of a short film produced in a school project in an extra-curricular theater “Lentera” at MTs and Nurul Huda Losari Vocational School.